ajutorrrrrr va rog frumos... e urgentttttttt:((((((((((((((((((((((((((((((((
Anexe:
Răspunsuri la întrebare
Răspuns de
0
a) 5a - 5b = 5(a - b)
b) (3x - 1)(x + 7) - (x + 7)(2x - 5) = (x + 7)(3x - 1- 2x + 5) =
(x + 7)(x + 4)
b) (3x - 1)(x + 7) - (x + 7)(2x - 5) = (x + 7)(3x - 1- 2x + 5) =
(x + 7)(x + 4)
alexandraaaaale:
ms
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă